1994
DOI: 10.1091/mbc.5.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Altered shape and cell cycle characteristics of fibroblasts expressing the E2F1 transcription factor.

Abstract: To gain an understanding of the role the E2F1 transcription factor plays in cell physiology, the full length protein (E2F1) and an amino terminal deletion of 87 amino acids (E2F1d87) were constitutively expressed in NIH3T3 fibroblasts. Multiple cell lines were generated for each construct. These cells do not proliferate in media containing low serum and do not proliferate in soft agar, indicating that they are likely not transformed. However, both sets of cell lines show increased DNA synthesis and increased n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Here we present evidence that the E2F1 transcription factor can directly in¯uence DNA replication, independent of any induction of apoptosis. The data are consistent with previous studies where the N terminal domain of E2F1 has been shown to a ect S phase progression in ®broblasts (Logan et al, 1994(Logan et al, , 1995. The inhibitory region of E2F1 appears to be located within its most N terminal 59 amino acids and does not require other functional domains, such as the cyclin A/cdk2 binding domain, the dimerization domain, the DNA binding domain, or the transactivation domain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here we present evidence that the E2F1 transcription factor can directly in¯uence DNA replication, independent of any induction of apoptosis. The data are consistent with previous studies where the N terminal domain of E2F1 has been shown to a ect S phase progression in ®broblasts (Logan et al, 1994(Logan et al, , 1995. The inhibitory region of E2F1 appears to be located within its most N terminal 59 amino acids and does not require other functional domains, such as the cyclin A/cdk2 binding domain, the dimerization domain, the DNA binding domain, or the transactivation domain.…”
Section: Discussionsupporting
confidence: 93%
“…The antiFlag M2 monoclonal antibody (Kodak) or an anti-HA monoclonal antibody (Promega) for E2F1D24 was diluted to 50 ng/ml in PBS plus 0.2% gelatin. Fifty ml of diluted antibody was added to a 6 cm tissue culture plate, coverslips containing the ®xed permeabilized cells were placed cell side down on the drop of diluted antibody and incubated for 1.5 h at 378C (Logan et al, 1994). The coverslips were washed three times in PBS plus 0.2% gelatin.…”
Section: Isolation Of Plasmid Dna/southern Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence, Confocal Microscopy, and Immunoprecipitation-Indirect immunofluorescence was performed as described by Logan et al (28). Briefly, COS cells were plated on 10-cm tissue culture dishes containing glass coverslips at approximately 500,000 cells/plate.…”
Section: Methodsmentioning
confidence: 99%
“…These numbers were derived from the percentage of chloramphenicol acetylation in each sample 1 2 3 4 5 6 7 8 9 10 1 2 3 4 5 6 7 8 9 10 _ _ E2F-1 (1-437) E2F-1 (88-437) Gst E2F-1 (1-437) E2F-1 (88-437) Gst a b Figure 6 E2F-1 binds to its responsive region on the TGF-b1 promoter. Increasing concentrations of puri®ed bacterially-produced recombinant GST-E2F-1 proteins (Logan et al, 1994;Krek et al, 1995) were examined for binding to the responsive region on the TGF-b1 promoter (a, lanes 2 ± 7) and to the consensus E2F-binding site on the DHFR promoter (b, lanes 2 ± 7). E2F-1 (1 ± 437) represents the full length version of the protein and the mutant E2F-1DN contains amino acids 88 ± 437.…”
Section: E2f-1 Binds To the Tiprs On The Tgf-b1 Promotermentioning
confidence: 99%